HISTORICAL AND SOCIOLINGUISTIC ASPECTS OF ENGLISH LOANWORDS IN THE KARAKALPAK LANGUAGE - Bakhbergenova, Akerke (International Conference on Science, Education & Law, 2026)
After the independence of Uzbekistan in 1991, the linguistic situation changed significantly. Globalization, technological progress, international education, and digital communication facilitated more direct contact with English. Consequently, modern English lexical units began entering the Karakalpak language both directly and indirectly. This study investigates the historical stages, sociolinguistic causes, and linguistic mechanisms of English loanword adoption in the Karakalpak language. The analysis demonstrates that the borrowing process can be divided into two major periods: indirect borrowing through Russian during the Soviet era and direct or mixed borrowing in the post-independence period. The research also identifies extralinguistic factors such as globalization, technological development, and economic transformation, as well as linguistic factors including nominative necessity and terminological precision. The findings highlight the dynamic nature of lexical borrowing and its role in the modernization and development of the Karakalpak lexicon.